Risk factor analysis of data from assessment clinics in the UK breast screening programme: a case-control study in Portsmouth and Southampton. Issue 2 (April 1996) - Thomas, E; Cade, J; Vail, A
Abstract : STUDY OBJECTIVES: The aim was to quantify the influence of demographic and reproductive factors on breast cancer. The subjects' path through the screening clinic, the inherent differences between the control groups, and the possible biases when using screening programmes were also considered. DESIGN: A case-control study using both personal contact and postal questionnaires to gather demographic and reproductive information. SETTING: Women attending two breast screening recall clinics in Portsmouth and Southampton over the period 1990-92. PARTICIPANTS: Altogether 1813 subjects between the ages of 50 and 65 years. The subjects' disease status was ascertained using a mammography and classified into four categories: 253 breast cancer (cases); 207 benign breast disease (BD); 410 requiring early rescreen (ER); and 943 for standard recall (SR). The BD, ER, and SR groups were used as separate controls. MAIN RESULTS: Of the factors considered here, the only two that showed a consistently significant effect on the risk of breast cancer were age and body mass index (BMI). Odds ratios were calculated for five yearly age groups and four groups of BMI using the youngest and lightest group as the baseline, respectively. There seemed to be an increase in the risk of breast cancer for increasing age for each comparison made (for cases v SR:OR (95% CI) = 1.60 (1.10, 2.34), 2.54 (1.76, 3.68)). All subjects above the lowest quartile of BMI experienced increased risk, although a trend was not clear (for cases v SR: OR (95% CI) = 1.66 (1.03, 2.66), 1.37 (0.86, 2.20), 1.98 (1.24, 3.15)). CONCLUSIONS: Various other potential risk factors were found to be inconsistently significant depending on choice of control group. This may help in understanding the differences between the three control groups used.